Maintenance management practiced by MARA (MRSM) / Mohd Darabi Zolkafli - Zolkafli, Mohd Darabi (Faculty of Architecture, Planning and Surveying, 2008)
Building maintenance management is one of the important aspects in any property management. The understanding of the building maintenance and its field area is a must for a professional Building Surveyor. Building maintenance covers not only on the building facilities itself, as the need nowadays become more and more complex i.e. changing on technology (technology movement and transferred), design requirements, organization management, financial, legal and by-law. Maintenance management is to maintain the building properly to an appropriate and acceptable standard at suitable cost with the minimum distraction to the occupier or tenants’ inconvenience. Maintenance management includes a review of existing policies, strategies and standards to ensure that they continue to achieve maintenance more efficient and effective. They should continue to support achievement of the agency’s services delivery objectives. Any changes required to meet the projected strategies business and portfolio directions and improve the efficiency and effectiveness of maintenance should be identified and described. Maintenance is a continuous operation to keep the school building, furniture and equipment in the best form for normal use and to ensure the use of the school building as a shelter in case of an emergency caused by natural hazards events. The school maintenance programme should be systematic and proactive to prevent the need for repairs. For Maktab Rendah Sains MARA is one of MARA building which the maintenance carried out by contractor. But contractor is engaged by MARA building through the open tender. Each of contractor can maintaining all MARA buildings to a country include MRSM. Since, there are several maintenance problems in the education building especially MRSM. Besides that, three MRSM or MARA Science Junior Colleges choose which MRSM Muar in Johor, MRSM Tun Ghafar Baba in Malacca and MRSM Kuala Kubu Bharu in Selangor. The aims research is focus the maintenance management carried out by contractor with maintenance management in MARA headquarters. Writer also make observation, interviews and distribute questionnaires to analysis the satisfaction of respondents about maintenance management at their place. Observation carried out is to inspection the real condition building and check the defect. Lastly, several propose to upgrading maintenance management by contractor and action by MARA also listed. Besides that, some the suggestion also proposed based on maintenance available.